The association between renal accumulation of pancreatic amyloid-forming amylin and renal hypoxia - Verma, Nirmal; Despa, Florin (Frontiers in Endocrinology, 2023)
Chronic kidney disease (CKD) is increasing worldwide and is associated with diabetic states (obesity, prediabetes and type-2 diabetes mellitus). The kidney is intrinsically susceptible to low oxygen (hypoxia) and renal hypoxia plays a vital role in the progression of CKD. Recent studies suggest an association between CKD and renal deposition of amyloid-forming amylin secreted from the pancreas. Renal accumulation of amyloid-forming amylin is associated with increased production of reactive oxygen species (ROS) and activation of hypoxia signaling in the kidney. In this review we will discuss potential associations between renal amylin amyloid accumulation and mechanism of hypoxia-induced kidney dysfunction, including activation of hypoxia-inducible factors (HIFs) and mitochondrial dysfunction.